2018
DOI: 10.1038/s41467-018-04296-4
|View full text |Cite
|
Sign up to set email alerts
|

Transient modes of zeolite surface growth from 3D gel-like islands to 2D single layers

Abstract: Zeolite crystallization occurs by multifaceted processes involving molecule attachment and nonclassical pathways governed by the addition of amorphous precursors. Here, we use scanning probe microscopy to monitor zeolite LTA crystallization in situ with a spatiotemporal resolution that captures dynamic processes in real time. We report a distinctive pathway involving the formation of gel-like islands from supersaturated solutions comprised of (alumino)silicate molecules. Three-dimensional assembly and evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 71 publications
6
104
1
1
Order By: Relevance
“…Zeolites can adopt several growth modes during assembly. 68 While at low supersaturation (e.g. at the end of crystallization, Stage IV) zeolites may grow via classical growth -implicating assembly from individual molecules to the growing crystal -they may also experience stages of nonclassical growth with particle attachment preceding disorder-to-order transformation.…”
Section: Molecular Al-assembly In Ssz-13mentioning
confidence: 99%
“…Zeolites can adopt several growth modes during assembly. 68 While at low supersaturation (e.g. at the end of crystallization, Stage IV) zeolites may grow via classical growth -implicating assembly from individual molecules to the growing crystal -they may also experience stages of nonclassical growth with particle attachment preceding disorder-to-order transformation.…”
Section: Molecular Al-assembly In Ssz-13mentioning
confidence: 99%
“…19 In this study we directly visualized the surface reconstruction of zeolite USY using atomic force microscopy (AFM), which is a widely used technique that is capable of capturing dynamic events of crystal surfaces at near molecular resolution. AFM has proven especially useful for examining the crystallization of zeolites and metal-organic frameworks (MOFs) that include LTA, 21 MFI, 22, 23 LTL, 24 SAV, 25 FAU, 26 CHA, 27 MOF-5, 26 and HKUST-1, 28 among others. [21][22][23][24][25][26] Rimer and coworkers 21 recently demonstrated the use of in situ AFM to illustrate the diverse precursors involved in the crystallization of zeolite LTA ranging from monomers and oligomers to nanocrystals and gel-like islands.…”
Section: Introductionmentioning
confidence: 99%
“…In situ AFM has proven to be a valuable technique for elucidating structural and dynamic characteristics of crystal growth mechanisms . Previously, it has been observed that struvite nucleation and growth on a brucite, Mg(OH) 2 , surface occurs via a particle‐mediated process suggesting a deviation from classical crystallization; however, the physicochemical properties of these particles remain elusive, as well as the exact mechanism of struvite crystallization, which could potentially involve multiple pathways, including classical ion/molecule addition.…”
Section: Resultsmentioning
confidence: 99%